PERBEDAAN SIKAP PROFESIONAL DILIHAT DARI STATUS PERKAWINAN GURU PAUD DI KECAMATAN SINGKIL KABUPATEN ACEH SINGKIL - Oktarini Fajriah; Peny Husna Handayani (JIP: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study was to determine the Difference in Professional Attitudes Viewed from the Marital Status of PAID Teachers in Singkil District, Aceh Singkil Regency. Thesis, Medan: Faculty of Education, State University of Medan 2025. This study uses a comparative research type. The sample in this study was 30 PAUD teachers, sampling using purposive sampling technique. The instruments used were questionnaires and observations. The statistical analysis used hypothesis testing using paired sample t-tests. The results of the study showed no significant difference between Professional Attitudes viewed from the Marital Status of PAID Teachers. This difference does not appear to be seen in the average value of the questionnaire and observation. The average obtained from the results of the questionnaire with the married group obtained a value of 8, while the results of the questionnaire with the unmarried group obtained a value of 7. The results of the average value obtained from the results of Observations 1 and 2 with the married group obtained 8, and the results of observations with the unmarried group obtained 7. The results of the data analysis obtained showed a significant value of 0.821> 0.05. Significance Value> 0.05 then Ho is accepted and Ha is rejected, meaning that there is no significant difference in Professional Attitudes seen from the Marital Status of PAID Teachers in Singkil District, Aceh Singkil Regency.